One-plasmid double-expression system for preparation of MS2 virus-like particles packaging SARS-CoV-2 RNA - Qi, Lili; Zhang, Zheng; Wang, Mengting; Ke, Zhijian; Mao, Haiguang; Deng, Gang; Wang, Jinbo (Frontiers in Cellular and Infection Microbiology, 2023)
Reverse transcription quantitative PCR (RT‒-qPCR) assay isassays are the gold standard molecular test for the detection of RNA virusviruses. The aim of this study was to construct an RNA-positive control based on MS2 phage-like particles (MS2 VLPs) to detect the RNA of SARS-CoV-2 RNA. pCDFDuet-1 was used as a one-plasmid double-expression system to construct MS2 VLPs containing ssRNA of SARS-CoV-2. The sequence encoding one copy of maturase, His-tag and coat protein dimer was cloned and inserted intointo MCS1 of the plasmid;. tThe fragment encoding protein N and ORF1ab from SARS-CoV-2 was cloned and inserted intointo MCS2 of the vector. The prepared plasmid was transformed into Escherichia. coli strain BL2 (DE3), and the expression of the construct was induced by 1 mM of isopropyl-L-thio-D-galactopyranoside (IPTG) at 30°C0 °C for 12 hours. MS2 VLPs were purified and collected with Ni-NTA affinity chromatography columns. The size and shape of the MS2 VLPs were verified of by transmission electron microscopy, and. tThe stabilityies of MS2 VLPsVLP packaged RNA were was evaluated by treatment with RNase A. The Eeffects of storage temperature and buffer on the stabilities of MS2 VLP stabilitys were also investigated. The results showed that SARS-CoV-2 MS2 VLPs could be successfully produced by this one-plasmid double-expression system. MS2 VLPs showed high stability and could may be used as thea positive control in the molecular diagnosis of COVID19COVID-19.